Analisis Value Terhadap Minat Penggunaan E-Toll Card Menggunakan Consumption Value Model (Studi Pada Pengguna Tol Surabaya-Gempol) - Karita Puspitasari; Yusi Tyroni Mursityo; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The compulsory usage of E-Toll Cards is a new policy introduced by the Indonesian government as a method for paying toll fee. Although the usage of E-Toll Cards are known to improve time efficiency of transactions, but it cannot be exactly pinpointed what affects time efficiency factor. If a factor can be identified, then that factor can be that intensified to improve efficiency of E-Toll Cards. The purpose of this research is to identify the values that are involved in usage of E-Toll Cards in 5 variables which are functional values, emotional values, epistemic values, conditional values and social values with 97 respondents. Results show that the functional value variable is the most significant, respondents agreed that using E-Toll Cards is the right solution to solving traffic jams on toll roads which is caused by long paying queues, and the results from paying services utilizing E-Toll Cards are as expected by the respondents. The findings from the epistemic value variables toward the current topic of research is that respondents agreed that the usage of E-Toll Cards for paying toll fares are a new method which was never implemented previously and the procedure of acquiring an E-Toll Card is relatively easy as it is readily available for purchase in bank branches all across Indonesia. The findings from the social value variables is that he needs of the respondents can be fulfilled with using E-Toll Cards and using E-Toll Cards because they want to give a good impression that they are law abiding citizens. Emotional value and conditional value variables are discovered to have no significance.